Diagnostic of the tourism system in the Lake Ranco basin (Revista LIDER, 2020)
In this essay the tourism system of the Ranco lake watershed is characterized and some potential tourist products are described for the comunas of Futrono and Lago Ranco. These analyses form part of the Plan de Ordenamiento Territorial de la Cuenca del Lago Ranco (LPT-UCT 2007), which is based on secondary informative data recollected, the implementation of participative workshops, and interviews with local actors, which has made it possible to quantify the primary tourist attractions of the watershed. The results show that for the comuna of Futrono, has 45 attractions in four tourism units (Futrono, Huapi, Llifén, and Maihue), while for the comuna of Lago Ranco´s 47 attractions were identified in four units (Nilahue, Rupumeika, Illahuape and Ranco). Among these attractions, those that are particularly unique are the volcanic systems, the Maihue and Ranco lakes, and the presence of the mapuche huilliche culture. We conclude that the Ranko Lake watershed possesses a potential for touristic development as much for its natural resources as for its historical-cultural patrimony.